Efektivitas Infusa Daun Talok (Muntingia calabura) dalam Menghambat Pertumbuhan Bakteri Klebsiella pneumoniae - Fitri Nadifah; Desto Arisandi; Siti Fatimah; Dani Setiawan (Penelitian dan Pengabdian Kepada Masyarakat Sekolah Vokasi Universitas Gadjah Mada, 2018)
Klebsiella pneumoniae is one of the most bacteria found in urine of Urinary Tract Infection (UTI) Patients. Study in many countries has found that this species become resistant to more than one antibiotics. This research goal is to know the effectiveness of talok (Muntingia calabura) infused water inhibiting the growth of K. pneumoniae. This was an experimental study using K. pneumoniae bacteria isolated from urine samples using diffuse agar method. The concentration of talok infused water was varied from 25-100% and the antibiotics used was cefotaxime, meropenem and chloramphenicol. The inhibition activity was measured by the diameter of inhibition zone. The results show that K. pneumoniae is still give sensitive response to antibiotic treatments. While the inhibition zone from talok infused water treatments can be categorized in middle and strong activity. From this study we can conclude that talok infused water potential in inhibiting the growth of K. pneumoniae. Future study still needed to develop this potential, especially for the bacteria that has been resistant to some antibiotics.